Cryocrystal phase transitions applied as temperature standards - Szmyrka-Grzebyk, A.; Kowal, A. (Физика низких температур, 2009)
International temperature scales define several fixed points, which temperature values are determined with a very high precision. Some of them, which are in a low-temperature range, are called gaseous fixed points because the reference substances under a normal condition — in a room-temperature range — appear in a gaseous state. These reference substances are called by physicists cryocrystals or quantum crystals when occurring in a low temperature in a solid state. The substances play an important role in a standard thermometry. The triple point of argon, oxygen, neon and hydrogen are primary fixed points of the International Temperature Scale of 1990 (ITS-90) [1]. The triple points of nitrogen, methane and carbon dioxide are secondary fixed points of the scale [2]. Also, the solid–solid phase transitions in the cryocrystals are secondary fixed points of the scale. The highest accuracy methods of measurements applied in a standard thermometry enable the determination with a very small uncertainty of the phase transition temperatures, its reproducibility and stability. The reproducibility and stability of the transition temperature are the most important factors deciding about usefulness of these points in thermometry. Using the highest accuracy methods, better than 1 mK, which at present are used in metrology only can give a new information about nature and properties of investigated substances important also for physicists.